Spatiotemporal treadmill gait measurements using a laser range scanner: feasibility study of the healthy young adults. (22nd March 2017) - Tanabe, S; Ii, T; Koyama, S; Saitoh, E; Itoh, N; Ohtsuka, K; Katoh, Y; Shimizu, A; Tomita, Y
Abstract: Objective: Spatio-temporal parameters are typically used for gait analysis. Although these parameters are measured by sophisticated systems such as 3D motion capture system or optoelectronic bars, these systems cannot be deployed easily because of their high costs, large space requirements and elaborate set-up. The purpose of this study is to develope a system for measuring spatiotemporal gait parameters using a laser range scanner during treadmill gait. Approach: To calculate accurate spatiotemporal parameters, the differences between the laser range scanner measured values and the reference values obtained from a 3D motion capture system were investigated in thirty subjects. From measurements in time and position at foot contact/off, adjustments to compensate for the differences in time and position were derived. Then, to determine the validity of the proposed system, values from the proposed system and the reference system were compared in four additional subjects. Main results: The results indicate that the data from the laser range scanner demonstrate certain differences in time and position compared with reference values. However, when compensation values were introduced, each spatiotemporal parameter correlated well with the reference values. Significance: This newer system is smaller, is easier to deploy and requires less training than the 3D motion capture system.